Interactions between π-conjugated chromophores in a giant molecular spoked wheel. Issue 2 (8th December 2016) - Würsch, D.; May, R.; Wiederer, G.; Jester, S.-S.; Höger, S.; Vogelsang, J.; Lupton, J. M.
Abstract : Single photon emission from a giant molecular spoked wheel due to excitonic coupling between the twelve distinct chromophores. Abstract : We discuss the intriguing photophysics of a giant molecular spoked wheel of π-conjugated arylene–alkynylene chromophores on the single-molecule level. This "molecular mesoscopic" structure, C1878 H2682, shows fast switching between the 12 identical chromophores since the fluorescence is unpolarised but only one chromophore emits at a time.